Taxonomic study on Scotiophyes Diakonoff from China, with the description of a new species (Lepidoptera: Tortricidae) - Wang, Xin-Pu (Zootaxa, 2009)
Scotiophyes subtriangulata, sp. nov., is described and illustrated. The new species is similar to S. faeculosa from which it can distinguished by the following: basal blotch and median fascia distinct; uncus subtriangular, narrowed gradually apically; sacculus smooth ventrally near base; arms of gnathos thick and short; and aedeagus slender. Photographs of adults and genitalia of S. faeculosa and S. subtriangulata are provided. A key to the known species of the genus is included. The type specimen of the new species is deposited in the Insect Collection of Nankai University, China.